Dynamic Interpretation of Emerging Risks in the Financial Sector - Hanley, Kathleen Weiss; Hoberg, Gerard (Review of Financial Studies, 2019)
[We use computational linguistics to develop a dynamic, interpretable methodology that can detect emerging risks in the financial sector. Our model can predict heightened risk exposures as early as mid-2005, well in advance of the 2008 financial crisis. Risks related to real estate, prepayment, and commercial paper are elevated. Individual bank exposure strongly predicts returns, bank failures, and return volatility. We also document a rise in market instability since 2014 related to sources of funding and mergers and acquisitions. Overall, our model predicts the buildup of emerging risk in the financial system and bank-specific exposures in a timely fashion.]